Investasi Perancangan Alat Pemberi Pakan pada Ayam Secara Otomatis guna Meningkatkan Produktivitas Kerja - Nurdianto, Noval Sigit; Purnama, Jaka (Fakultas Teknik Universitas Tulang Bawang, 2025)
This research aims to design and develop automatic chicken feeding equipment to increase work efficiency, productivity and farmer profits. Using the productivity calculation method before the equipment is designed, feeding requires 3 workers with a time of 15 minutes per session. After implementing the tool, labor requirements were reduced to 2 people with only 10 minutes per session. Using the HPP (Cost of Production) calculation method, this tool is able to increase work productivity by 3.3% and increase farmer profits from IDR 24,196 to IDR 26,924 per day. Based on the payback period calculation, this tool is able to return investment costs within 5 days, with an average expenditure of IDR 592,328 per day. This automatic chicken feeder is designed with the ability to set operational times at 08.00, 16.00 and 24.00, and has a feed capacity of 10 kg/day. The research results show that this tool is effective in increasing the operational efficiency of chicken farms, thereby providing significant benefits for farmers. Keywords: Automatic, Effective, Productivity